[tex]a_{n} = n^{2}-2n\\\\a_{n+1} = (n+1)^{2}-2(n+1) = n^{2}+2n+1 -2n-2 = n^{2}-1\\\\r = a_{n+1} - a_{n} = n^{2}-1 - (n^{2}-2n) = n^{2}-1-n^{2}+2n = 2n-1 > 0[/tex]
Jeżeli różnica ciągu jest > 0, to ciąg jest rosnący, zatem ten ciąg jest rosnacy.
[tex]n^{2}-2n = 120\\\\n^{2}-2n-120 = 0\\\\\Delta = (-2)^{2} - 4\cdot(-120) = 4 + 480 = 484\\\\\sqrt{\Delta} = \sqrt{484} = 22\\\\n \in N+\\\\n_1 = \frac{-(-2)-22}{2} = \frac{-20}{2} = -10, \ odrzucamy\\\\n_2 = \frac{-(-2)+22}{2} = \frac{24}{2} = 12\\\\a_{12} = 12[/tex]
Odp. Dwunasty wyraz ciągu jest równy 120.